Epigenetic Regulation of Dental Pulp Stem Cell Fate - Dan Zhou; Lu Gan; Yiran Peng; Yachuan Zhou; Xin Zhou; Mian Wan; Yi Fan; Xin Xu; Xuedong Zhou; Liwei Zheng; Wei Du (Hindawi Limited, 2020)
Epigenetic regulation, mainly involving DNA methylation, histone modification, and noncoding RNAs, affects gene expression without modifying the primary DNA sequence and modulates cell fate. Mesenchymal stem cells derived from dental pulp, also called dental pulp stem cells (DPSCs), exhibit multipotent differentiation capacity and can promote various biological processes, including odontogenesis, osteogenesis, angiogenesis, myogenesis, and chondrogenesis. Over the past decades, increased attention has been attracted by the use of DPSCs in the field of regenerative medicine. According to a series of studies, epigenetic regulation is essential for DPSCs to differentiate into specialized cells. In this review, we summarize the mechanisms involved in the epigenetic regulation of the fate of DPSCs.